Comparison of EuroQol-5D-3L and Short Form-6D Utility Scores in Family Caregivers of Colorectal Cancer Patients: A Cross-Sectional Survey in China - Sun, Cheng-yao; Liu, Yang; Zhou, Liang-ru; Wang, Ming-si; Zhao, Xian-ming; Huang, Wei-dong; Liu, Guo-xiang; Zhang, Xin (Frontiers in Public Health, 2021)
Abstract Objective: To compare EuroQol-5D-3L (EQ-5D-3L) and Short Form-6D (SF-6D) utility scores in family caregivers (FCs) of colorectal cancer patients. Method: This study was performed on FCs (family caregivers) with colorectal cancer from three primary cancer centers in Heilongjiang province’s capital city. All subjects were enrolled and filled the EQ-5D-3L, along with SF-6D questionnaires. Two tools were compared for their distribution, discriminant validity, agreement, convergent validity along with known-groups validity. Result: 292 FCs of colorectal cancer patients were enrolled. The score distribution of SF-6D along with EQ-5D-3L were not normal. A ceiling impact was seen in 31.8% of FCs for EQ-5D-3L, however none for SF-6D. Good associations (Spearman’s rho = 0.622, p < 0.01) and Intraclass correlation (ICC 0.637 and average ICC 0.778) between the two scores. EQ-5D-3L yielded higher utility scores in contrast with SF-6D in the better health subclass. SF-6D distinguished better between excellent and good health status, with better effect size and relative efficiency statistics. Both tools showed good known-groups validity. Conclusion: Utility scores of SF-6D were remarkably lower relative to that of EQ-5D-3L, but the difference may be clinically insignificant. However, the SF-6D may be superior because of the lack of ceiling impact. SF-6D exhibited better convergent validity along with discrimination validity of excellent health condition, and improved known-groups validity efficiency.